1992
DOI: 10.1144/gsjgs.149.3.0349
|View full text |Cite
|
Sign up to set email alerts
|

Silurian turbidite provenance and the closure of Iapetus

Abstract: Subduction of Iapetus crust during the Caledonian orogeny has been seen by some authors as terminating at the end of Ordovician times and by others as continuing through the Silurian. We present petrological and chemical data which support a coeval arc origin for detritus in the Lettergesh Formation (Silurian), western Ireland. The arc, based on continental crust, lay to the north of the present outcrops of this formation, along the Laurentian margin of Iapetus, implying active oceanic subduction in the Siluri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…The Lettergesh sandstones have a significant detrital volcanic component. It has been suggested that the rapid deposition of such a thick sedimentary succession was related to a major volcanic episode near the basin at this time (Williams, O'Connor & Menuge, 1992;Menuge, Williams & O'Connor, 1995). The deposition of the sandstones resulted in the accumulation of some 1300 m (compacted) of sediment between the uppermost Llandovery and the Lower Wenlock, possibly over two to three million years.…”
Section: Conglomerates and Sea-level Variationmentioning
confidence: 98%
“…The Lettergesh sandstones have a significant detrital volcanic component. It has been suggested that the rapid deposition of such a thick sedimentary succession was related to a major volcanic episode near the basin at this time (Williams, O'Connor & Menuge, 1992;Menuge, Williams & O'Connor, 1995). The deposition of the sandstones resulted in the accumulation of some 1300 m (compacted) of sediment between the uppermost Llandovery and the Lower Wenlock, possibly over two to three million years.…”
Section: Conglomerates and Sea-level Variationmentioning
confidence: 98%
“…The Wenlock epoch is regarded as the time when the Iapetus and Tornquist oceans closed (Williams, O'Connor & Menuge, 1992;Trench & Torsvik, 1992;Soper et al 1992). A waning subduction zone, with thickening crust, can give rise to alkaline magmas rich in HFSE and with potassic affinities, such as are found today in the form of shoshonite lavas at Stromboli, Aeolian Islands, which lies above 18 km of continental crust (Francalanci, Manetti & Peccerillo, 1989).…”
Section: Source and Tectonic Settingmentioning
confidence: 99%
“…In Europe, early Wenlock tus reported from northern Eire (area 2a, Figure 9) are the ®nal expression of an episode of early Silurian volcanism on the Laurentian margin of Iapetus associated with continental collision (Williams et al 1992). The Wenlock tus and lavas of the Dingle Peninsula (area 2, Figure 9) are mentioned above (in the Intoduction).…”
Section: Nearby Wenlock Volcanismmentioning
confidence: 93%